A pilot feasibility study exploring the effects of a moderate time-restricted feeding intervention on energy intake, adiposity and metabolic physiology in free-living human subjects. (30th August 2018) - Antoni, Rona; Robertson, Tracey M.; Robertson, M. Denise; Johnston, Jonathan D.
Abstract: This pilot study explored the feasibility of a moderate time-restricted feeding (TRF) intervention and its effects on adiposity and metabolism. For 10 weeks, a free-living TRF group delayed breakfast and advanced dinner by 1·5 h each. Changes in dietary intake, adiposity and fasting biochemistry (glucose, insulin, lipids) were compared with controls who maintained habitual feeding patterns. Thirteen participants (29 (sem 2) kg/m 2 ) completed the study. The average daily feeding interval was successfully reduced in the TRF group (743 (sem 32) to 517 (sem 22) min/d; P  < 0·001; n 7), although questionnaire responses indicated that social eating/drinking opportunities were negatively impacted. TRF participants reduced total daily energy intake ( P  = 0·019) despite ad libitum food access, with accompanying reductions in adiposity ( P  = 0·047). There were significant between-group differences in fasting glucose ( P  = 0·008), albeit driven primarily by an increase among controls. Larger studies can now be designed/powered, based on these novel preliminary qualitative and quantitative data, to ascertain and maximise the long-term sustainability of TRF.